ПЕДАГОГИЧЕСКАЯ СИСТЕМА РАЗВИТИЯ НАВЫКОВ СОВМЕСТНОЙ РАБОТЫ У ЧЛЕНОВ КЛАССНОГО КОЛЛЕКТИВА ПОСРЕДСТВОМ КОЛЛОБРОТИВНЫХ ТЕХНОЛОГИЙ - Бекмуратов, К. (SCIENCE and SOCIETY, 2025)
The article examines the pedagogical system of developing students’ collaborative work skills through collaborative technologies. The theoretical foundations of collaborative learning, as well as key principles and methods that contribute to effective interaction between students within the class collective, are considered. Special attention is paid to modern digital platforms and tools that ensure the creation of conditions for joint activities. The work analyzes various approaches to organizing collaborative learning, such as project methodology, group discussion, and role-playing games, with emphasis on the teacher’s role in the process of forming group dynamics and evaluating results.